ROS and DNA repair in spontaneous versus agonist-induced NETosis: Context matters - Azzouz, Dhia; Palaniyar, Nades (Frontiers in Immunology, 2022)
Reactive oxygen species (ROS) is essential for neutrophil extracellular trap formation (NETosis). Nevertheless, how ROS induces NETosis at baseline and during neutrophil activation is unknown. Although neutrophils carry DNA transcription, replication and repair machineries, their relevance in the short-lived mature neutrophils that carry pre-synthesized proteins has remained a mystery for decades. Our recent studies show that (i) NETosis-inducing agonists promote NETosis-specific kinase activation, genome-wide transcription that helps to decondense chromatin, and (ii) excess ROS produced by NADPH oxidase activating agonists generate genome-wide 8-oxy-guanine (8-OG), and the initial steps of DNA repair are needed to decondense chromatin in these cells. These steps require DNA repair proteins necessary for the assembly and nicking at the damaged DNA sites (poly ADP ribose polymerase PARP, apurinic endonuclease APE1 and DNA ligase), but not the enzymes that mediate the repair DNA synthesis (DNA polymerases and PCNA). In this study, we show that (i) similar to agonist-induced NETosis, inhibition of early steps of oxidative DNA damage repair proteins suppresses spontaneous NETosis, but (ii) the inhibition of late stage repair proteins DNA polymerases and PCNA drastically promotes baseline NETosis. Hence, in the absence of excessive ROS generation and neutrophil activation, DNA repair mediated by PCNA and DNA polymerases is essential to prevent chromatin decondensation and spontaneous NETosis. These findings indicate that ROS, oxidative DNA damage, transcription and DNA repair differentially regulate spontaneous and agonist-induced NETosis. Therefore, context matters.